보행 보조도구에 따른 일상생활활동 훈련프로그램이 엉덩관절치환술 환자의 일상생활 수행 능력과 작업치료 인식도 및 만족도에 미치는 효과 - 홍은기; 방요순; 손보영 (대한작업치료학회지, 2022)
목적 : 본 연구는 일상생활활동 훈련프로그램을 적용하여 엉덩관절치환술 환자의 일상생활 수행 능력과 작업치료 인식도 및 만족도에 미치는 효과를 알아보고자 하였다. 연구방법 : 본 연구는 엉덩관절치환술을 받은 노인 40명(실험군 20명, 대조군 20명)이었고, 연구 설계는비동등성 대조군 전후시차 설계를 적용하였다. 중재는 주 5회 30분씩, 4주간, 총 20회기를 실시하였다. 결과 : 일상생활활동 훈련프로그램 실험군은 일상생활활동 비디오 시청 대조군과 비교하여 일상생활 수행능력과 작업치료 인식도 및 만족도에서 유의한 차이를 나타냈다. 결론 : 본 연구의 일상생활활동 훈련프로그램은 엉덩관절치환술을 받은 노인들의 일상생활 수행 능력과 작업치료 인식도 및 만족도를 향상시키어 작업치료의 전문성과 가치를 높였다. 이에 엉덩관절치환술 환자의 재활을 위한 작업치료 중재 프로그램으로 제안하는 바이다. Objective: This study aimed to determine the effects of applying an ADL training program on the ADL performanceability, occupational therapy awareness, and satisfaction of patients after a total hip replacement. Methods: The study subjects were 40 elderly patients having a total hip replacement (20 in the experiment groupand 20 in the control group), and the applied study design was a nonequivalent control group with anon-synchronized design. The intervention was conducted for 30 minutes, five times a week for four weeks, fora total of 20 sessions per group. Results: The results showed that the experiment group, which participated in the ADL training program,demonstrated a significant increase in ADL performance ability and occupational therapy awareness andsatisfaction compared to the control group, which only watched ADL training program videos. Conclusion: The ADL training program used in this study demonstrated the importance of expertise and value ofoccupational therapy by improving the ADL performance ability and occupational therapy awareness andsatisfaction of elderly patients after a total hip replacement. Thus, this study recommends the ADL trainingprogram as an occupational therapy intervention for the rehabilitation of patients after a total hip replacement. KCI Citation Count: 0